Towards rationalizing the use of economic sanctions - Gabriel Felbermayr; Clifton T. Morgan; Constantinos Syropoulos; Yoto Yotov (Austrian Institute of Economic Research (WIFO), 2024)
The remarkable increase in the use of economic sanctions as a coercive tool of foreign policy over the past quarter century has been accompanied by an equally rapid growth in the number of academic and policy studies, which most often aim at quantifying the economic effects of sanctions and/or understanding the reasons for their success or failure. Interestingly, the sanctions literature has failed to answer convincingly a seemingly simple but fundamental question: Why are sanctions used in the first place? To fill this gap, we build on developments in the conflict and bargaining literatures to propose a theory that motivates the imposition of economic sanctions. We also highlight the practical relevance of our framework and discuss how it can be extended to capture additional sanction features, which are assumed away in the benchmark model.
Keywords: F13; F51; H59; N40; N70; 330; Economic Sanctions; Military Conflict; Bargaining Theory